Availability of Tertiary Education for People with Disabilities in Poland - Gilga, Krystyna (Studia Oeconomica Posnaniensia, 2015)
Education is one of essential social services. Access to tertiary education is limited for disabled people. There are far fewer disabled graduates than others. The aim of the paper is to present activities undertaken by universities in order to facilitate education for the disabled. The activities presented are based on legal regulations as well as the concept that a disabled person being a citizen.